2020
DOI: 10.1101/2020.09.15.298455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TDP-43 stabilizes transcripts encoding stress granule protein G3BP1: potential relevance to ALS/FTD

Abstract: TDP-43 nuclear depletion and concurrent cytoplasmic accumulation in vulnerable neurons is a hallmark feature of progressive neurodegenerative proteinopathies such as amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Cellular stress signalling and stress granule dynamics are now recognized to play a role in ALS/FTD pathogenesis. Defective stress granule assembly is associated with increased cellular vulnerability and death. G3BP1 (Ras-GAP SH3-domain-binding protein 1) is a critical stress g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 74 publications
(112 reference statements)
0
7
0
Order By: Relevance
“…regions, with the longer transcript being the predominant one expressed in the cerebellum compared to the frontal cortex (Sidibé et al, 2020). This implies that the relevance of this regulatory mechanism may vary within the CNS.…”
Section: Regulation Of G3b P1 Mrnamentioning
confidence: 99%
See 4 more Smart Citations
“…regions, with the longer transcript being the predominant one expressed in the cerebellum compared to the frontal cortex (Sidibé et al, 2020). This implies that the relevance of this regulatory mechanism may vary within the CNS.…”
Section: Regulation Of G3b P1 Mrnamentioning
confidence: 99%
“…Indeed, TDP-43 depletion results in decreased G3BP1 protein levels (McDonald et al, 2011) and recent work has uncovered that this is because of TDP-43 binding and stabilizing the short G3BP1 transcript via a conserved 16-nt element located within the 3'UTR (Sidibé et al, 2020). This work also demonstrated that G3BP1 mRNA levels are compromised in ALS/ FTD neurons featuring TDP-43 inclusions with concomitant nuclear depletion (Sidibé et al, 2020). Whether this is also true in other diseases featuring TDP-43 pathology remains to be demonstrated.…”
Section: Regulation Of G3b P1 Mrnamentioning
confidence: 99%
See 3 more Smart Citations